Exome Sequencing Identifies a Novel MAP3K14 Mutation in Recessive Atypical Combined Immunodeficiency - Schlechter, Nikola; Glanzmann, Brigitte; Hoal, Eileen Garner; Schoeman, Mardelle; Petersen, Britt-Sabina; Franke, Andre; Lau, Yu-Lung; Urban, Michael; van Helden, Paul David; Esser, Monika Maria; Möller, Marlo; Kinnear, Craig (Frontiers in Immunology, 2017)
Primary immunodeficiency disorders (PIDs) render patients vulnerable to infection with a wide range of microorganisms, and thus provide good in vivo models for assessment of immune responses during infectious challenges. Priming of the immune system, especially in infancy, depends on different environmental exposures and medical practices. This may determine the timing and phenotype of clinical appearance of immune deficits as exemplified with early exposure to bacille Calmette-Guerin (BCG) vaccination and dissemination in combined immunodeficiencies. Varied phenotype expression poses a challenge to identification of the putative immune deficit. Without the availability of genomic diagnosis and data analysis resources and with limited capacity for functional definition of immune pathways, it is difficult to establish a definitive diagnosis and to decide on appropriate treatment. The present study describes the use of exome sequencing to identify a homozygous recessive variant in MAP3K14, NIKVal345Met, in a patient with combined immunodeficiency, disseminated BCG-osis and paradoxically elevated lymphocytes. Laboratory testing confirmed hypogamma-globinaemia with normal CD19, but failed to confirm a definitive diagnosis for targeted treatment decisions. NIKVal345Met is predicted to be deleterious and pathogenic by two in silico prediction tools, and is situated in a gene crucial for effective functioning of the non-canonical nuclear factor-κB (NF-κB) signalling pathway. Functional analysis of NIKVal345Met- versus NIKWT-transfected HEK293T cells showed that this mutation significantly affects the kinase activity of NIK leading to decreased levels of phosphorylated IKKα, the target of NIK. BCG-stimulated RAW264.7 cells transfected with NIKVal345Met also presented with reduced levels of phosphorylated IKKα, significantly increased p100 levels and significantly decreased p52 levels compared to cells transfected with NIKWT. Ideally, these experiments would have been conducted in patient-derived immune cells, but we were unable to source these cells from the patient. The functional analysis described in this paper supports previous illustrations of the importance of NIK in human immune responses, and demonstrates the involvement of function-altering mutations in MAP3K14 in PIDs. The genomic approach used for this patient demonstrates its value in the diagnosis of an unusual PID and as a tool for detecting rarer mutations to help guide treatment approaches.